a Rekonstruksi Etika Seksualitas Kristen: Kajian Teologis-Etis terhadap Fenomena Hidup Bersama Tanpa Pernikahan di Kalangan Jemaat - Tyson Supit (STT INDONESIA MANADO, 2026)
Abstract: Sexuality is a gift from God that must be realised within the bond of marriage as a sacred covenant reflecting love and moral responsibility. Shifts in values brought about by culture and globalisation, as well as popular culture, present new challenges for the church in upholding the integrity of Christian sexual ethics whilst providing a contextual response to the realities of congregational life. The phenomenon of cohabitation without marriage (kumpul kebo), which is beginning to be observed amongst Christian congregations, indicates a tension between theological teachings on the sanctity of marriage and increasingly permissive social practices. This study aims to analyse and reconstruct Christian sexual ethics through a theological-ethical approach as a response to the phenomenon of cohabitation without marriage amongst Christian congregations. Using a qualitative method with a library research approach, it can be concluded that Christian sexual ethics are grounded in the theology of creation, the concept of the imago Dei, and marriage as a sacred covenant that forms the basis for the expression of human sexuality. The theological-ethical analysis reveals that the phenomenon of cohabitation without marriage amongst Christian congregations is influenced by social and cultural changes, as well as a weakening of faith formation. This study reconstructs Christian sexual ethics through a paradigm that integrates truth and pastoral care as an ethical model that remains grounded in biblical authority. Abstrak: Seksualitas merupakan anugerah Allah yang harus diwujudkan dalam ikatan pernikahan sebagai perjanjian kudus yang mencerminkan kasih dan tanggung jawab moral. Pergeseran nilai akibat budaya dan globalisasi, serta budaya populer menimbulkan tantangan baru bagi gereja dalam mempertahankan integritas etika seksualitas Kristen sekaligus memberikan respons yang kontekstual terhadap realitas kehidupan jemaat. Fenomena hidup bersama tanpa pernikahan (kumpul kebo) yang mulai dijumpai di kalangan jemaat Kristen menunjukkan adanya ketegangan antara ajaran teologis mengenai kekudusan pernikahan dengan praktik sosial yang semakin permisif. Penelitian ini bertujuan menganalisis dan merekonstruksi etika seksualitas Kristen melalui pendekatan teologis-etis sebagai respons terhadap fenomena hidup bersama tanpa pernikahan di kalangan jemaat Kristen. Menggunakan metode kualitatif dengan pendekatan studi kepustakaan (library research), maka dapat disimpulkan bahwa etika seksualitas Kristen berlandaskan pada teologi penciptaan, konsep imago Dei, dan pernikahan sebagai perjanjian kudus yang menjadi dasar ekspresi seksualitas manusia. Analisis teologis-etis mengungkapkan bahwa fenomena hidup bersama tanpa pernikahan di kalangan jemaat Kristen dipengaruhi oleh perubahan sosial, budaya, dan melemahnya pembinaan iman. Penelitian ini merekonstruksi etika seksualitas Kristen melalui paradigma yang mengintegrasikan kebenaran, dan pendampingan pastoral sebagai model etika yang tetap berlandaskan otoritas alkitabiah.